Pengembangan Bahan Ajar Bahasa Arab untuk Meningkatkan Keterampilan Berbahasa Siswa Kelas VIII MTs YPPA Cipulus - Dasep Bayu Ahyar; Salsa Amelia Putri Ramadani; Muhammad Habillah Gifaril; Muhamad Redi Yudistira; Eli Herawati; Zaenur Ropiq; Moh. Yandi Ramdhani (Program Studi Pendidikan Bahasa Arab, 2024)
This study aims to develop effective Arabic Language Teaching Materials in improving the language skills of class VIII students at Mts YPPA Cipulus, The research method used is the development research method which involves the planning, development, and evaluation stages of teaching materials. Data was collected through Observation, Interviews and the data we obtained. The results of the study indicate that the teaching materials developed in the institution are able to improve students' Arabic language skills. The practical implication of this study is the importance of developing teaching materials that are in accordance with students' needs to improve the quality of Arabic language learning at the secondary school level.